Teaching multiculturalism in a pre school classroom - Alves, Inês Mendes Erse (2016)
The following study is the Master Dissertation in Early Childhood and Primary Education at Instituto Superior de Educação e Ciências in Lisbon. Education plays a powerful role in influencing a child´s development and contributing to who they will one day become and according to Souto-Manning (2013) “multicultural education seeks to respect the humanity of every person, prioritizing the teachers´ and children´s personal, practical knowledge as foundational to promoting change in early childhood settings and beyond.” (p.7). Therefore, the purpose of this study is to (1) provide increased understanding of multicultural education along with strategies for planning and implementing a multicultural curriculum for a preschool audience and (2) to demonstrate to educators the benefits of a Multicultural Exchange Project in Early Childhood Education. The Multicultural Exchange Project that will be presented in this study was accomplished within the Supervised Teaching Practice in Preschool Education. This Project represents the collaboration between two five-year-old classrooms from two different countries – Portugal and Malawi –. The preschoolers in both classrooms created and exchanged books to help their friends in the other country understand their city, country, language, traditions, music and food. There was also an exchange of other gifts, such as, a handmade puzzle of the Portuguese flag, recipes, photographs and presentation of videos of music and traditional dances. The two groups of children participated in two Skype sessions; since they spoke different languages it was necessary for the teachers to be translators. The findings of this study clearly demonstrate that openness and respect for differences between very different cultures can be effectively addressed through intentional multicultural instruction in the preschool classroom.